2017
DOI: 10.1111/ppa.12732
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the build‐up of Plasmodiophora brassicae inoculum by early management of oilseed rape volunteers

Abstract: Clubroot of oilseed rape (OSR), caused by Plasmodiophora brassicae, is a disease of increasing economic importance worldwide. Previous studies indicated that OSR volunteers, Brassica crops and weeds play a critical role in the predisposition of the disease. To determine the effect of timing of foliar application of the herbicide glyphosate or mechanical destruction of OSR volunteers in reduction of clubroot severity and resting spore production, a series of studies was conducted under controlled conditions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…In contrast to the less virulent pathotype, growing plants in soil infested with the high virulent P. brassicae isolate induced the most rapid increase in root fresh weight, resulting in a statistically significant increase in the number of new resting spores inside the roots. These findings were very similar to our previous study under controlled conditions, where we showed that the first symptoms of clubroot are observed as early as 7 days post-inoculation, and that the severity of symptoms and the root fresh weight of inoculated plants both increased over time and were strongly correlated with higher numbers of pathogen resting spores [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the less virulent pathotype, growing plants in soil infested with the high virulent P. brassicae isolate induced the most rapid increase in root fresh weight, resulting in a statistically significant increase in the number of new resting spores inside the roots. These findings were very similar to our previous study under controlled conditions, where we showed that the first symptoms of clubroot are observed as early as 7 days post-inoculation, and that the severity of symptoms and the root fresh weight of inoculated plants both increased over time and were strongly correlated with higher numbers of pathogen resting spores [25].…”
Section: Discussionsupporting
confidence: 92%
“…Besides the susceptible oilseed rape crop, oilseed rape volunteer seedlings as well as other Brassica crops and weeds can play a critical role in the maintenance of resting spores in infested fields. As such, early destruction of oilseed rape plants and volunteers in clubroot-infested fields has been shown to limit the increase of P. brassicae resting spore numbers in the soil [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The erosion of the effectiveness of CR genes has also occurred in cruciferous vegetables in Asia ( Bhattacharya et al, 2014 ; Chai et al, 2014 ). The elevated infection in clubroot-resistant cultivars and volunteers would lead to increased spore load of the pathogen in the soil ( Zamani-Noor and Rodemann, 2017 ). Hence, clubroot remains a huge problem and poses by far the most significant threat to cruciferous crop production worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetative growth spanned three principal stages at our location in southern China: bud (00-09), leaf (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and shoot (31)(32)(33)(34)(35)(36)(37)(38)(39) development. The growth cycle of S. mukorossi differed from those of longan and lychee trees in southern China; these latter species have a period of dormancy in winter after completing the growth of shoot and then start the reproductive period in the spring of next year.…”
Section: Discussionmentioning
confidence: 99%